Integrating Spirituality and Modern Life: The Neo-Sufism Vision of Kiai Agoes Ali Masyhuri - Aini, Nurul; Aswadi (Journal of Islamic Philosophy and Contemporary Thought, 2023)
Contemporary has been revitalized through Neo-Sufism, which offers spiritual solutions to the crisis of meaning in modern society. This study uses a qualitative approach based on a literature review and biographical analysis to trace the dynamics of Kiai Agoes Ali Masyhuri’s (Gus Ali) thought. The analysis reveals that Gus Ali creatively adapts the principles of al-Ghazālī’s Sufism to address contemporary spiritual and social challenges. Gus Ali’s Neo-Sufism emphasizes the importance of active engagement in society, the strenghtening of values of nobility, well-being, and peace, as well as the utilization of digital technology in da‘wah. He integrates spirituality into daily life without getting caught up in mystical exclusivism, encouraging practical reflection and positive contributions to social life. This study affirms that neo-Sufism not only preserves the spiritual roots of Islam but also demonstrates its adaptive capacity in facing the changes of the times. Thus, Gus Ali’s approach enriches the discourse on Islamic renewal form below, affirming the continuity and relevance of the Islamic spritual heritage in the modern era.